2020
DOI: 10.4236/gep.2020.84006
|View full text |Cite
|
Sign up to set email alerts
|

Study of Internal Waste Dump-Induced Shear Stress Behavior on Pit-Slope

Abstract: Regardless of beneficial associated with internal waste dump (IWD) method, practices of this method within boundaries of pit-slope have some serious problems on stability issues due to this area is zone of potential failure. This zone is known as dynamic reactive zone which is easy to deform by external force, and inherent dangers of failure posing a threat to slope. Therefore, it is paramount to study the induced shear stress behavior in this zone particularly when IWD method is adopted within this zone. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Wahyudi et al [37] explore the application of numerical study for investigating IWDinduced shear stress behavior using FEM with the strength reduction approach in The "shear strength reduction method" is the method relating to the strength reduction factor. It is important to determine the value of FS that will merely result in the slope failure achieving the correct SRF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wahyudi et al [37] explore the application of numerical study for investigating IWDinduced shear stress behavior using FEM with the strength reduction approach in The "shear strength reduction method" is the method relating to the strength reduction factor. It is important to determine the value of FS that will merely result in the slope failure achieving the correct SRF.…”
Section: Resultsmentioning
confidence: 99%
“…Wahyudi et al [37] explore the application of numerical study for investigating IWDinduced shear stress behavior using FEM with the strength reduction approach in different scenarios as per pit-slope depths. Based on the finding, it is found that shear stress imposed on the pit slope seems to change dramatically with increasing IWD height for cases in which the buffer zone length is less than 100 m. When the height of the internal dump is set at 30 m, the FEM SRF is 0.86, the Bishop method SRF = 0.749, the Janbu simplified method SRF = 0.737, and the Spencer simplified method SRF = 0.745.…”
Section: Resultsmentioning
confidence: 99%
“…Rock dumping with the formation of a solid slope can be directly performed from the surface or with a multitier formation of internal dumps [38]. The location of internal dumps within the boundaries of an open-pit slope can lead to serious problems related to its stability, because this zone is potentially destructive and can easily deform under the influence of external loading from mining equipment [39]. The placement of rocks in the mined-out space of a deep open pit, taking into account the technological schemes for the development of mining operations, is based on determining a safety factor for the dump slopes and the safe distance for mining equipment operation [40,41].…”
Section: Introductionmentioning
confidence: 99%